Identifying behavioral and neural correlates of observational avoidance learning in rats - Ruble, Shannon (My University, 2025)
Social interactions enrich the lives of individuals while also providing valuable information about the environment and appropriate behaviors. Observational learning, a form of social learning, allows individuals to learn about potential outcomes in an environment without directly experiencing those outcomes. Prior research has investigated how individuals learn fear through observation, but little is known about how individuals learn to avoid danger through observation. We therefore modified the platform-mediated avoidance (PMA) task to understand how rats (Observers) learn to avoid a tone-signaled footshock by observing another rat (Demonstrator) perform the task. We found that pre-exposure to a single footshock enhanced Observers’ learning when Observers witnessed a Demonstrator undergoing early, but not late, stages of PMA training. Additionally, we found evidence that Observers may shift from utilizing avoidance strategies after observing early stages of PMA, to utilizing freezing strategies after observing late stages of PMA. To better understand the neural mechanisms underlying observational avoidance learning, we used c-Fos immunohistochemistry to quantify neural activation in the anterior cingulate cortex (ACC) and the infralimbic cortex (IL) since prior work has implicated these regions in observational learning and fear and avoidance learning, respectively. Surprisingly, we found no differences in ACC activation between Observers and Demonstrators. Conversely, the IL showed increased activation in shock pre-exposed Observers compared to Demonstrators and shock-naïve Observers. These findings provide insight into how different brain regions may be recruited to perform the same behavior depending on prior experiences.
Keywords: Active avoidance; Anterior cingulate cortex; Infralimbic cortex; Observational learning